Analisis Tugas Dan Wewenang Dinas Kebersihan Dan Pertamanan Dalam Pengelolaan Sampah Rumah Tangga Dan Industri (Studi Pada Kota Bandar Lampung) - Lintje Anna Marpaung (PRANATA HUKUM, 2013)
Some problems that occur in terms of waste management in the City of Bandar Lampung, that the large volume of waste generated by the people of Bandar Lampung, so it requires the optimization of the role of Hygiene and Gardens Department of Bandar Lampung City in management of waste at coastal areas. The duties and authorities Sanitation Department of Bandar Lampung in the management of household and industrial waste consisting of: Implement the Waste Management Operations Technical stages collecting system, garbage collection, transportation to the place of final disposal and system of disposal to landfill of Bakung. Implement Institutional Systems and Waste Management Organization. Factors inhibiting the duties and authority of the Department of Hygiene and Bandar Lampung in the management of household and industrial waste are: Lack of awareness of the public to dispose of waste in place, Lack of community participation in waste management,Â No maximum participation of the private sector in waste management.